Meningkatkan Minat Belajar Melalui Metode Projeck Based Learning dengan Media Loosepart - Sulastini Sulastini; Wahira Wahira; Kahrul Alam (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to find out the Increase in Interest in Learning Through the Project Based Learning Method With Loosepart Media group B IN TK-ALHALIIM pademawu. The research method is class action research, with the subject of the study being students of TK Al-Haliim totals of 15 children. Data collection is carried out by observation and the results of children's work when carrying out activities. The data collected will be analyzed using a correlation of product moments with a quantitative approach. Based on the results of the hypothesis, it was found that 0% of children in the undeveloped category, 6.6% began to develop, 3,3 developed as expected, and 80% of children in the category of developing very well, meaning that there was an influence on the application of based learning methods on children's interest in completing learning activities.